The Novel in the Age of Disintegration : Dostoevsky and the Problem of Genre in the 1870s - Holland, Kate (Book collections on Project MUSE., 2013)
Scholars have long been fascinated by the creative struggles with genre manifested throughout Dostoevsky's career. In this book, the author shows that Dostoevsky aimed to use the form of the novel as a means of depicting the disintegration caused by various crises in Russian society in the 1860s. This required him to reinvent the genre. At the same time, he sought to infuse his novels with the capacity to inspire belief in social and spiritual reintegration, and to this end, he returned to old forms and structures that were already becoming outmoded. In thoughtful readings of Demons, The Adolescent, A Writer's Diary, and The Brothers Karamazov, the author delineates Dostoevsky's struggle to adapt a genre to the reality of the present, with all its upheavals, while maintaining a utopian vision of Russia's future mission.